2014
DOI: 10.5433/1679-0359.2014v35n2p605
|View full text |Cite
|
Sign up to set email alerts
|

Extração de mucilagem e substratos no desenvolvimento de plântulas de maracujazeiro-amarelo

Abstract: ResumoO objetivo deste trabalho foi avaliar diferentes métodos de extração da mucilagem e também substratos na emergência e no desenvolvimento de plântulas de maracujazeiro-amarelo, em câmara de nebulização. Foram utilizados cinco métodos de extração da mucilagem das sementes (água; água + areia; água + cal virgem; liquidificador com lâminas protegidas e fermentação em água) e três tipos de substratos (casca de arroz carbonizada, vermiculita e fibra de coco). O delineamento experimental foi inteiramente casual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 3 publications
4
15
1
4
Order By: Relevance
“…In this way, Pereira and Dias (2000), Martins et al (2006) and Aguiar et al (2014) observed that fermentation did not influence the germination of P. edulis seeds, as observed in this study. Conversely, São José and Nakagawa (1987) noticed that extraction by fermentation method improved the quality of P. edulis seeds.…”
Section: Experiments Isupporting
confidence: 68%
See 3 more Smart Citations
“…In this way, Pereira and Dias (2000), Martins et al (2006) and Aguiar et al (2014) observed that fermentation did not influence the germination of P. edulis seeds, as observed in this study. Conversely, São José and Nakagawa (1987) noticed that extraction by fermentation method improved the quality of P. edulis seeds.…”
Section: Experiments Isupporting
confidence: 68%
“…However, studies on other species have shown positive results (Martins et al, 2006;Osipi et al, 2011;Aguiar et al, 2014;Araújo et al, 2015). Similarly, Silva (2012) relates that this method promotes a chemical seed scarification causing the breakage and abrasion of the sarcotesta, which increase the water permeability and germination, as seen in this study.…”
Section: Experiments Isupporting
confidence: 52%
See 2 more Smart Citations
“…This knowledge would ensure high crop yields (Meletti et al, 2002). Removal of aryl is directly related to methods for obtaining high quality seeds (Aguiar et al, 2014;Araújo et al, 2015). Besides other techniques conducted in the development of plants, such as pruning (Almeida, 2012a), soil fertilization (Almeida, 2012b), seed storage (Araújo et al, 2009) and the use of a suitable substrate in seedling formation (Wagner Junior et al, 2007;Aguiar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%